Piano Trios, op. 1, nos. 1-3 (Pacini) - Beethoven, Ludwig van, 1770-1827 (composer):::Creator:::::::::::: (France; Paris; Pacini, 2024)
Early edition of the Piano Trios in E-flat major, G major, and C minor, published in Paris by Pacini.